The Intersective Influence of Race and Gender on the Career Advancement of Black Women Faculty at Predominantly White Institutions - Delaney, Linda; Okojie, Stephen (Advances in Social Sciences Research Journal, 2025)
This study critically examined the intersective influence of race and gender on the career pathways of Black women faculty at predominantly white institutions (PWIs). Using a qualitative research design, this study examined the unique challenges and barriers encountered by the study participants, as well as the opportunities within the academic landscape. Eighteen Black female faculty members participated in the study, providing rich narratives that highlight the intersective influence of race and gender on their career advancement. The findings revealed widespread systemic inequalities that hindered their career advancement, in addition to personal stories that showcase resilience and resistance in the face of adversity. This research contributes to the growing body of knowledge on intersectionality by highlighting the need for transformative reforms to promote diversity, equity, and inclusion in higher education. The results show that systemic obstacles, such as microaggressions and cultural taxation, significantly impacted the professional experiences of Black female faculty. However, through resilience, community support, and strategic navigation, the participants demonstrated remarkable strength and resourcefulness. The study discusses implications for institutional policies and practices, calling for a reevaluation of existing frameworks used in faculty evaluation and promotion. Ultimately, this research offered practical recommendations for creating an inclusive academic environment that values diversity and provides equitable opportunities for all faculty members.